CO2 emissions and mitigation policies for urban road transportation: Sao Paulo versus Shanghai - Costa, Evaldo (2020)
This paper compares the energy consumption, CO 2 emissions and public policies of two mega-cities, Sao Paulo (SP) and Shanghai (SH), in order to identify their GHG emissions mitigation policies. Both cities have experienced rapid growth of the automotive sectors resulting in sizable pollution and CO 2 emission challenges. SP has successfully implemented the ethanol and encouraged the growth of the fleet of light-duty vehicles. SH has coal-based power generation and restricted the ownership of the vehicles in an attempt to reduce GHG emissions, invested in public transportation and electric mobility. Tabular analysis of secondary data was adopted in this study, revealing also that SP has considerably expanded individual transportation. Despite investments in ethanol, the city could not contain the increase in CO 2 emissions from road transportation. SH invested in public transportation and inhibited individual transportation, but also failed to contain CO 2 emissions. Mitigation policies and measures taken were not sufficient to prevent growth of CO 2 emissions in both cities. To reduce CO 2 emissions in transportation, SP and SH should focus on public policies to encourage public and clean transportation and limit the burning of fossil fuels.